BAGAIMANA IMPLEMENTASI STRATEGI ALIANSI MEREK MEMPENGARUHI EKUITAS MEREK DAN KETERLIBATAN KONSUMEN? (TINJAUAN LITERATUR SISTEMATIS) - Shabrina Aulia Adam (CV. Denasya Smart Publisher, 2026)
Increasing business competition encourages firms to adopt innovative marketing strategies to strengthen their brand position in the market. One strategy that has gained significant attention is brand alliance, which refers to collaboration between two or more brands to create added value for both companies and consumers. This strategy is believed to enhance brand equity and foster consumer engagement through brand synergy, shared resources, and enriched brand experiences. However, previous studies remain fragmented and have not yet provided a comprehensive understanding of how brand alliance implementation simultaneously influences brand equity and consumer engagement. Therefore, this study aims to examine the impact of brand alliance strategies on brand equity and consumer engagement using a systematic literature review approach. The research method follows the PRISMA framework by reviewing reputable international journal articles published between 2014 and 2024 through stages of identification, screening, and in-depth analysis. From an initial pool of 237 articles, 19 relevant studies were selected for further examination. The findings reveal that brand alliance implementation generally has a positive effect on brand equity, particularly in terms of perceived quality, brand credibility, and brand loyalty. In addition, brand alliance is found to enhance consumer engagement by fostering emotional involvement, interactive experiences, and higher perceived value. Nevertheless, the effectiveness of this strategy is highly dependent on brand fit, the level of alliance integration, and appropriate communication strategies. This study concludes that brand alliance is a promising strategic approach for building long-term competitive advantage when it is carefully designed and strategically managed.